The iron and oxygen abundances in the metal-poor star HD 140283 and in the Sun - Shchukina, N.G.; Vasiljeva, I.E.; Trujillo Bueno, J. (Кинематика и физика небесных тел, 2005)
We present the results of a theoretical investigation of the impact of NLTE effects and of granulation inhomogeneities on the iron and oxygen abundances in the metal-poor star HD140283 and in the Sun. Our analysis is based on both the classical one-dimensional (1D) stellar atmosphere models and on a new generation of three-dimensional (3D) hydrodynamical models. We consider the Sun as a reference star. The solar iron and oxygen abundances are redefined.